2019
DOI: 10.1039/c9dt00604d
|View full text |Cite
|
Sign up to set email alerts
|

Subunit–subunit interactions play a key role in the heme-degradation reaction of HutZ fromVibrio cholerae

Abstract: Heme degradation reaction of HutZ from Vibrio cholerae is regulated by the subunit–subunit interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(38 citation statements)
references
References 60 publications
5
33
0
Order By: Relevance
“…Recent studies by our group further showed that subunit-subunit interactions play a key role in the heme degradation reaction [16]. The distance between heme and Trp109, which reflects subunit-subunit orientational changes, was increased from [16][17][18] Å for wild-type HutZ to 23-25 Å for R92A and R92L mutant enzymes, similar to data obtained for mutants of Ala31 [16], His63 [19] and Asp132. Based on the collective results, we propose an activation mechanism of HutZ involving conformational changes at Arg92, which are transmitted to the heme axial ligand His170 through Ala31, His63, and Asp132, with modulation of subunit-subunit interactions.…”
Section: Introductionsupporting
confidence: 81%
See 4 more Smart Citations
“…Recent studies by our group further showed that subunit-subunit interactions play a key role in the heme degradation reaction [16]. The distance between heme and Trp109, which reflects subunit-subunit orientational changes, was increased from [16][17][18] Å for wild-type HutZ to 23-25 Å for R92A and R92L mutant enzymes, similar to data obtained for mutants of Ala31 [16], His63 [19] and Asp132. Based on the collective results, we propose an activation mechanism of HutZ involving conformational changes at Arg92, which are transmitted to the heme axial ligand His170 through Ala31, His63, and Asp132, with modulation of subunit-subunit interactions.…”
Section: Introductionsupporting
confidence: 81%
“…Heme degradation activity was also pH-dependent; HutZ is active at pH 6.0, but it is inactive at pH >7.0 [16]. In view of the correlation between the high-spin heme content and heme degradation activity, we propose that heme degradation activity of HutZ is related to the high-spin heme content [16].…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations